Glycyrrhiza Glabra L. Suppress the Proliferation of Non-Small Cell Lung Cancer by Inducing Necrosis Rather Than Apoptosis Despite Increasing Bax Level - Rios-Ramirez, M (Taylor and Francis Ltd., 2025)
Lung cancer remains the leading cause of cancer-related mortality worldwide, highlighting the urgent need for the development of novel therapeutic agents. Glycyrrhiza glabra, a medicinally significant plant, is known for its rich composition of diverse phytochemicals. However, its role in the induction of apoptosis in lung cancer cells has not been well elucidated. The present study aimed to evaluate the apoptosis-associated cytotoxic and antiproliferative effects of Glycyrrhiza glabra methanol extract (GGME) on non-small cell lung cancer (A549) cells. The viability of GGME-treated A549 cells was assessed using an MTT assay, which revealed a significant antiproliferative effect at 200 µg/ml (p < 0.05). Morphological changes were observed via phase-contrast inverted microscopy. To elucidate the mode of cell death, Annexin V/PI staining was performed, and the mRNA levels of the pro-apoptotic Bax and anti-apoptotic Bcl-2 genes were quantified by real-time PCR. Interestingly, while Bax expression increased 4-fold (p < 0.01) compared to the control, Bcl-2 levels remained unchanged. Despite this pro-apoptotic shift in gene expression, the cells predominantly underwent necrotic cell death rather than apoptosis. Furthermore, LC-MS/MS analysis identified vanillic acid, fumaric acid, syringic acid, and thymoquinone as the major compounds in GGME. In conclusion, GGME exerts a antiproliferative effect primarily through necrosis rather than apoptosis. © 2025 Informa UK Limited, trading as Taylor & Francis Group.